Guidelines for Tax Collection Development of Luang Prabang Province - Lathtanaphoubai, Bounthanom; Phomlasaboud , Khantavan; Somsacksaisompheng , Oulavieng (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Tax revenue collection to fully meet targets remains a major issue and a significant challenge for the Lao PDR. Therefore, this study aims to examine the opinions of service users regarding tax collection and explore approaches for improving tax revenue collection in the jurisdiction of Luang Prabang Province. This study used questionnaires as a tool to collect data from taxpayers receiving services in Luang Prabang Province, with a sample group of 224 respondents. The data were analyzed using the SPSS program version 2025 to analyse ( ) and standard deviation (SD). The results of the study indicate that tax collection and its development in Luang Prabang Province should be improved in several areas, including service quality, service equipment, modern technology, staff knowledge and capacity, public information dissemination, development of applications for online tax payment channels, expansion of tax payment service points, and the implementation of a one-stop banking system for tax payments.